Optimal Joint Design of Discrete Fractional Fourier Transform Matrices and Mask Coefficients for Multichannel Filtering in Fractional Fourier Domains - Zhang, X.; Ling, B.; Dam, Hai Huyen Heidi; Teo, Kok Lay; Wu, Changzhi (IEEE, 2018)
The concept of mask operation in fractional Fourier domains is a generalization of the conventional Fourier-based filtering in the frequency domain. It is known that simultaneously employing multiple mask operations in multiple different fractional Fourier domains can lead to significant performance advantages when compared with just employing a single mask operation in a single fractional Fourier domain. However, there is no systematic scheme for optimal joint design of the discrete fractional Fourier transform (DFrFT) matrices and the corresponding sets of mask coefficients. In this paper, we consider this design problem and construct a formulation that does not depend on the knowledge of noise statistics. We then develop an iterative algorithm, which is a hybrid descent (HD) approach, to solve the formulated optimization problem. For this HD approach, a gradient descent method is supplemented by a modified simulated annealing algorithm. It is employed to find the global optimal rotation angles of the DFrFT matrices. During the iterative process, the corresponding sets of mask coefficients can be constructed analytically. Simulation results demonstrate that the proposed scheme is highly effective.